Synthesis of Ceramics in Different Colors from Industrial Waste - Doynov, Mihail; Dimitrov, Tsvetan; Kokkori, Maria (International Journal of Ecology, 2013)
The synthesis of arsenic-free ceramics from industrial waste is studied. Samples of waste containing siliceous material passed the exploitation leap-guard layer shift reactor whose main oxide is γ-Al2O3 and, with the addition of natural raw materials and pure oxide, arsenic-free ceramics were synthesized with thermal and electrical properties related to the main phase of spinel group minerals; solid solutions were also formed in the process of synthesis. Insulating properties were established by successive heating and cooling of the specimen for six cycles. Electrical insulating properties were established by the method of resistance to arcing. The relative density was determined by hydrostatic method and diffusion lines of molecules at the main phase were characterized by X-ray diffraction analysis. The experimental procedures followed in this study allowed mixing on a molecular level due to the small dimensions of the crystallite which in turn explains the relatively high density.